IMPLEMENTATION OF THE "SIAGA BANKID" PORTAL, A DAILY AGENDA MANAGEMENT INFORMATION SYSTEM TO IMPROVE ACCESSIBILITY OF ACTIVITY PLANS AT THE DISTRICT OFFICE OF BANDUNG KIDUL - Pamoedjie, Pramuditya; Kurniawati, Rina (INFOKOM (Informatika & Komputer), 2025)
Administration at the sub-district level faces efficiency challenges, particularly in manual and fragmented agenda coordination and mail distribution. Reliance on conventional methods such as instant messaging groups (WhatsApp) often leads to miscommunication, inefficiency, and difficulties in activity recapitulation. This study aims to create a centralized and accurate information center by implementing the web-based portal "SIAGA BANKID" (Bandung Kidul Sub-district Activity Agenda Accessibility Information System). This study uses the System Development Life Cycle (SDLC) methodology with a prototyping model, which includes user needs identification, rapid design, prototype development, and iterative evaluation to ensure the system meets real-world needs. The result of this study is a functional portal with key features such as structured agenda input, an interactive activity calendar display, role-based user management, notifications, and a sophisticated search function. The implementation of this portal has proven effective in simplifying coordination and significantly increasing efficiency. By providing a comprehensive overview of activity plans, this system supports accountability and effectiveness of administrative governance at the Bandung Kidul Sub-district Office.